1998
DOI: 10.1161/01.cir.98.10.969
|View full text |Cite
|
Sign up to set email alerts
|

Increased Availability and Open Probability of Single L-Type Calcium Channels From Failing Compared With Nonfailing Human Ventricle

Abstract: Individual L-type calcium channels are fundamentally affected in severe human heart failure. This is probably important for the impairment of cardiac excitation-contraction coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
194
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(212 citation statements)
references
References 44 publications
14
194
0
2
Order By: Relevance
“…In hypertrophied guinea pig hearts, inhomogeneous changes in I Ca,L were considered to contribute to a transmurally heterogeneous prolongation of ventricular APD (4). Schroder et al (39) found that single Ca 2ϩ channels exhibited increased availability and opening probability in cells isolated from failing human hearts, but whole cell I Ca,L did not show significant differences, when compared with nonfailing cells, in agreement with a previous report in humans (27). Recently, it has been found that the L-type Ca 2ϩ channel number is reduced and channel open times are increased in ventricular cells from pacing-induced canine failing hearts, so that overall I Ca,L density is unchanged (10).…”
Section: Discussionmentioning
confidence: 99%
“…In hypertrophied guinea pig hearts, inhomogeneous changes in I Ca,L were considered to contribute to a transmurally heterogeneous prolongation of ventricular APD (4). Schroder et al (39) found that single Ca 2ϩ channels exhibited increased availability and opening probability in cells isolated from failing human hearts, but whole cell I Ca,L did not show significant differences, when compared with nonfailing cells, in agreement with a previous report in humans (27). Recently, it has been found that the L-type Ca 2ϩ channel number is reduced and channel open times are increased in ventricular cells from pacing-induced canine failing hearts, so that overall I Ca,L density is unchanged (10).…”
Section: Discussionmentioning
confidence: 99%
“…Single-channel recordings were performed by using the cell-attached configuration of the patchclamp method as described (35). Cells were placed in disposable Petri dishes containing 3 ml of a high-potassium depolarizing solution [25 mM KCl͞120 mM potassium glutamate͞2 mM MgCl 2 ⅐6H 2 O͞10 mM Hepes͞2 mM EGTA͞10 mM dextrose͞1 mM CaCl 2 ͞1 mM Na 2 -ATP (pH 7.3) with KOH].…”
Section: Methodsmentioning
confidence: 99%
“…Openings and closures were identified by the half-height criterion. The fraction of active sweeps within a channel-containing patch (availability), the open probability within active sweeps (open probability), and the peak value of single-channel ensemble average currents (I peak ) were determined as described (35). In double-channel patches, these parameters were corrected for the number of channels as described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Similar reduction of I to and I K1 has been observed in ventricular cells isolated from failing human hearts. 3,17 In terms of I Ca,L , various changes such as an increase, 18 no change, 19 and a decrease 20 in the density of I Ca,L have been reported in myocytes of failing human hearts. In BIO 14.6 hamsters, the density of I Ca,L was significantly depressed at the late heart failure stage, although it was unaltered at 20 weeks (unpublished observations).…”
Section: Matsumoto Et Al Et a Receptor Blockade On Electrical Remodelingmentioning
confidence: 99%